The first stars: formation, properties, and impact - Klessen, Ralf S.; Glover, Simon (Annual review of astronomy and astrophysics, 2023)
The first generation of stars, often called Population III (or Pop III), form from metal-free primordial gas at redshifts z ∼ 30 and below. They dominate the cosmic star-formation history until z ∼ 15–20, at which point the formation of metal-enriched Population II stars takes over. We review current theoretical models for the formation, properties, and impact of Pop III stars and discuss existing and future observational constraints. ...